Personal Brand on Social Media through Creativity: Analysis of the Influencer 'Marcela Peraz' - Parra-Meroño, María Concepción; De-Juan-Vigaray, María D (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Consolidating a personal brand on social media is not an easy task. It requires a continuous learning process based on trial and error. However, once a good reputation is achieved and a connection with the audience is established, the possibility of generating both economic and personal benefits opens up. This work presents a success story of personal branding through creativity: 'Marcela Peraz', a content creator on social media, positioned as one of the best makeup and body paint artists in Latin America, with a prominent presence on TikTok, Facebook, Instagram, and YouTube.